Simple and sensitive spectrophotometric methods for the determination of acebutolol hydrochloride in bulk sample and pharmaceutical preparations - Manjunatha, Hadagali D.; Shaikh, Sarfaraj Mohd Takhi; Harikrishna, Kasalanti; Sudhirkumar, Ramanaboyina; Kandagal, Pradeep Basavaraj; Seetharamappa, Jaldappa (Eclética Química, 2008)
A direct, extraction-free spectrophotometric method has been developed for the determination of acebutolol hydrochloride (ABH) in pharmaceutical preparations. The method is based on ionpair complex formation between the drug and two acidic dyes (sulphonaphthalein) namely bromocresol green (BCG) and bromothymol blue (BTB). Conformity to Beer’s law enabled the assay of the drug in the range of 0.5-13.8 μg mL-1 with BCG and 1.8-15.9 μg mL-1 with BTB. Compared with a reference method, the results obtained were of equal accuracy and precision. In addition, these methods were also found to be specific for the analysis of acebutolol hydrochloride in the presence of excipients, which are co-formulated in the drug.